Action in Complexity: Entanglement and Emergent Order in Entrepreneurship. (March 2023) - Leong, David
When properly understood in the context of entrepreneurship, entanglement explains the complex ingredients in the tangled relations required for entrepreneurial success. However, in examining entrepreneurial success, many scholars overlook a critical consideration—are the right resources (people and materials) in the right place at the right time? How do entanglement and convergence come about? This occurs when a microsystem is entangled with many fine-grained structures with different degrees of freedom, converging to generate emergence. These fine-grained structures are the heterogeneous agents with correlated histories (co-founders, financiers, suppliers, competitors, customers, employees, etc.) that are entangled with the entrepreneurs. This article explains the complex causes in the emergent order arising from several entangled dynamics among the heterogeneous agents and resources. The challenge is understanding what complex ingredients and combinations are necessary for a new emergent order that gives rise to such possibilities. Finally, such emergence arising from entanglement is discussed to explain collaboration and coevolution effects, and suggestions for future research that utilises the intended theorisations of practice are offered.